DNA Methyltransferase 3B Gene Promoter and Interleukin-1 Receptor Antagonist Polymorphisms in Childhood Immune Thrombocytopenia - Margarita Pesmatzoglou; Marilena Lourou; George N. Goulielmos; Eftichia Stiakaki (Clinical and Developmental Immunology)
Primary immune thrombocytopenia (ITP) is one of the most common blood diseases as well as the commonest acquired bleeding disorder in childhood. Although the etiology of ITP is unclear, in the pathogenesis of the disease, both environmental and genetic factors including polymorphisms of TNF-a, IL-10, and IL-4 genes have been suggested to be involved. In this study, we investigated the rs2424913 single-nucleotide polymorphism (SNP) (C46359T) in DNA methyltransferase 3B (DNMT3B) gene promoter and the VNTR polymorphism of IL-1 receptor antagonist (IL-1 Ra) intron-2 in 32 children (17 boys) with the diagnosis of ITP and 64 healthy individuals. No significant differences were found in the genotype distribution of DNMT3B polymorphism between the children with ITP and the control group, whereas the frequency of allele T appeared significantly increased in children with ITP (P = 0.03, OR = 2, 95% CI: 1.06–3.94). In case of IL-1 Ra polymorphism, children with ITP had a significantly higher frequency of genotype I/II, compared to control group (P = 0.043, OR = 2.60, 95% CI: 1.02–6.50). Moreover, genotype I/I as well as allele I was overrepresented in the control group, suggesting that allele I may have a decreased risk for development of ITP. Our findings suggest that rs2424913 DNMT3B SNP as well as IL-1 Ra VNTR polymorphism may contribute to the susceptibility to ITP.